Theological Argument for the Molondhalo Tradition Held by the Gorontalo Ethnic Community - Sofyan A.P. Kau; Zulkarnain Suleman (Ulumuna, 2015)
Molondhalo is one of the traditions preserved by the Muslim community of Gorontalo. This tradition concerns “touching” the stomach of a pregnant woman at the seventh month of the pregnancy. In Javanese community, this tradition is called Mitoni, in Acehnese Peusijuek, in Sundanese Tingkeban, and in Balinese community magedong-gedongan. Within the Molondhalo ritual, there are cultural attributes, and recital of safety prayer (ngadisalawati) with a set of hulante and polutube. Some of these molondalo traditional practices gain critics from the outsider, i.e. puritan Muslims, because such a ritual practice exposes the awrat (part of the bodies that should be covered) and is said to have been infuenced by Hinduism. This article is not intended to merely address those challenges, but also to show some of the theological arguments of this custom/tradition based on the interpretation of the philosophy of the Gorontalonese community: “Adati hula-hulaa to sara’a, sara’a hula-hulaa to qur’ani” (Custom is based on shari’a, shari’a is based on the Qur’an). DOI: http://dx.doi.org/10.20414/ujis.v19i2.331